Philosophy and politics in the thought of John Wyclif - Lahey, Stephen E. (Cambridge studies in medieval life and thought, 2003)
John Wyclif was the fourteenth-century English thinker responsible for the first English Bible, and for the Lollard movement. In contrast with most other commentaries, this book argues that Wyclif's political programme was based on a coherent philosophical vision ultimately consistent with his earlier reformative ideas.